2009
DOI: 10.1016/j.transproceed.2009.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Kidney Transplant Recipients: Risk Factors and Effects of Vitamin D3 Supplements

Abstract: Introduction. The Kidney Disease Outcome Quality Initiative (K/DOQI) clinical practice guidelines in chronic kidney disease (CKD) give some recommendations about diagnosis and treatment of vitamin D deficiency. These guidelines may also be applied to renal transplant recipients. The aim of the present study was to assess the vitamin D status and the effects of vitamin D3 supplements among a cohort of kidney graft recipients. Patients and Methods. Five hundred nine renal transplant recipients with a follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 12 publications
4
20
1
Order By: Relevance
“…Suboptimal VD levels are commonly detected in kidney transplant recipients (KTRs), with prevalence of VD sufficiency below 20% [69]. Similar findings were detected in our institution in patients with duration of kidney transplantation (KTx) more than 6 months (n = 289), [70], During winter-spring fall, during the annual nadir of 25VD, the share of VD sufficient KTRs follow-up in our center dropped to 2.59% [71].…”
Section: Impaired Vitamin D Metabolism After Kidney Transplantation: supporting
confidence: 74%
“…Suboptimal VD levels are commonly detected in kidney transplant recipients (KTRs), with prevalence of VD sufficiency below 20% [69]. Similar findings were detected in our institution in patients with duration of kidney transplantation (KTx) more than 6 months (n = 289), [70], During winter-spring fall, during the annual nadir of 25VD, the share of VD sufficient KTRs follow-up in our center dropped to 2.59% [71].…”
Section: Impaired Vitamin D Metabolism After Kidney Transplantation: supporting
confidence: 74%
“…This may be related to pretransplantation prevalent traditional and nontraditional cardiovascular risk factors that can be aggravated by the effects of immunosuppressive drugs. Recent studies showed that vitamin D deficiency, which is very prevalent in the transplantation population [8,9], may have a role in endothelial dysfunction in patients with CKD besides its well-known effects on calcium and phosphorus metabolism [10,11].…”
mentioning
confidence: 99%
“…In one study, transplant recipients, who were an average of 7 years post-transplant, had significantly lower levels of 25(OH)D than age-matched controls [43]; among transplant patients mean serum 25(OH)D was 10 ng/ml and one-third of patients had undetectable levels [43]. Factors associated with low 25(OH)D in renal transplant recipients include African-American race [46], female sex, measurement in autumn and winter months [46], recent transplantation [55], inadequate dietary vitamin D intake, reported in 87e91% of patients [56], proteinuria [57], and use of ACE inhibitors or aldosterone receptor blockers [55]. Persistent elevations in FGF-23 after kidney transplantation may result in lower calcitriol levels [58].…”
Section: Vitamin D Deficiency In Long-term Transplant Recipientsmentioning
confidence: 99%
“…Vitamin D deficiency is common and severe in patients several years after kidney transplantation [43,46,55]. In one study, transplant recipients, who were an average of 7 years post-transplant, had significantly lower levels of 25(OH)D than age-matched controls [43]; among transplant patients mean serum 25(OH)D was 10 ng/ml and one-third of patients had undetectable levels [43].…”
Section: Vitamin D Deficiency In Long-term Transplant Recipientsmentioning
confidence: 99%